A review of the history of studying the Permian bony fish of European Russia - A.S. Bakaev (Учёные записки Казанского университета: Серия Естественные науки)
This article reviews the history of research on bony fish from the Permian of European Russia, summarizing the key findings that enable a deeper understanding of their evolution. The following three stages were singled out: primary data acquisition (from the first half to the end of the 19th century), compilation of the obtained data (from the early 20th century to the 1960s), and in-depth analysis of the accumulated data pool (from the 1970s to the early 21st century). The first stage began with the early published descriptions of the Permian fish remains from copper sandstones. These descriptions were also expanded by impressive studies performed by many famous scientists of the 19th century (J.G. Fischer von Waldheim, E. Eichwald, R.I. Murchison, and others) who searched for other animal and plant remains in this locality. In the second stage, the accumulated data were classified as a response to the advances in taxonomy and stratigraphy. The descriptions became more detailed: they were often supplemented with drawings and references to both systematic positions of the identified taxa and stratigraphic positions of the bone-bearing rocks based on the first regional stratigraphic schemes. During that time, the largest contributors to the study of the bony fish fauna of the region were B.P. Krotov, A.V. Khabakov, and L.S. Berg. The current stage is associated with the geological surveys that have been carried out in the region since the second half of the 20th century. They proved to be helpful for the excavation, dating, and subsequent analysis of fish remains. The most important findings were made by A.V. Minikh, M.G. Minikh, D.N. Esin, and D.I. Yankevich. This review is of high value because it presents the major events in the history of studying bony fish from the Permian of European Russia as a three-phased process, as well as discusses the main achievements, problems, and gaps related to it.